Cardiopulmonary assessment, quality induction and tracheal intubation with the use of induction adjunct with propofol in dogs - Cabala, Raquel Wolff; da Silva, Elisângela Barboza; Clark, Rosana Maria de Oliveira (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Cabala R.W., Silva E.B. & Clark R.M.O. [Cardiopulmonary assessment, quality induction and tracheal intubation with the use of induction adjunct with propofol in dogs.] Avaliação cardiorrespiratória, qualidade de indução e intubação orotraqueal com o uso de coadjuvantes na indução anestésica com propofol em cães. Revista Brasileira de Medicina Veterinária, 38(1):39-44, 2016. Escola de Veterinária, Universidade Federal de Minas Gerais, Av. Antônio Carlos, 6627, Caixa Postal 1567, Campus Pampulha, Belo Horizonte, MG 31270-901, Brasil. E-mail: raquelcabala@yahoo.com.br The objective was to evaluate the effects of the use of fentanyl, ketamine or diazepam, as coadjuvant induction of anesthesia with propofol in dogs and to evaluate the cardiovascular, respiratory and quality of induction of anesthesia and tracheal intubation by these agents. Twenty four dogs ASA I and II, of different breeds and average weight 18 ± 6.8 kg, males and females subjected to different surgical procedures were randomly allocated in four groups of six each: G-CP (saline); G-FP (5mcg/kg - fentanyl), G-KP (0,5 mg/kg - ketamine) and G-DP (0,2mg/kg - diazepam). All animals recieved pre-anaesthetic medication with acepromazine (0,05 mg/kg) combined with morphine (0,2 mg/kg) administered intramuscularly. Two minutes after coadjuvants or saline administration, the anaesthetic induction was perfomed with 5mg/kg of propofol or the sufficient dose required to lost protector reflex and ensure endotracheal intubation. HR, SAP, MAP, DAP, RR, ETCO2, SpO2, and To C were measured before pre-anaesthetic medication (M1), 15 minutes after M1 (M2), during induction of anesthesia (M3), at the end of induction anesthetic (M4) and after intubation (M5). The quality of anesthesia was evaluated using a numerical scale by induction and intubation score. The use of fentanyl as co-adjuvant induction reduced significantly propofol dose requirement (2,42±0,38mg/kg), when compared to G-CP (4,43±0,32mg/kg), to G-DP (3,78±1,3mg/kg) and to G-KP (3,90±0,84mg/kg). Significant reductions on arterial pressures ocurred in G-FP, but it were similar in G-CP. No statistically significant differences were observed between groups in mean HR, RR, ETCO2 , SpO2 and To C. SpO2 was reduced in M4 of G-DP. The induction and intubation scores were similar in all groups. The administration of fentanyl decreased propofol requirement but promoted severe hypotension when compared with other co-adjuvants agents. There were minimal undesirable effects. The quality of induction and intubation were satisfactory, but the dogs that were induced with only propofol demonstrated better score.